Energy and exergy analysis of perforated twisted tapes: RSM-driven optimization of geometrical parameters for PV/T systems - Goksu, Taha Tuna; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2025)
Photovoltaic/thermal systems encounter efficiency constraints as a result of overheating in photovoltaic modules. This study presents perforated twisted tapes (PTT) as a new insert type for PV/T systems aimed at improving thermal and electrical performance. A numerical analysis using CFD investigated 27 different PTT geometries, varying in hole diameter (0.5-1.5 mm), hole count (1-3), and spacing between holes (2-3 mm), under laminar flow conditions. Energy and exergy analyses measured the electrical and thermal efficiency, while performance evaluation criteria (PEC) assessed the hydro-thermal gains. Statistical analysis of the collected data was conducted utilizing response surface methodology. Results indicate that PTT inserts significantly lower the PV surface temperature (minimum: 308.4 K) and the fluid outlet temperature (minimum: 303.4 K). The optimized geometry (d = 0.5 mm, N = 1, s = 2 mm) attained a peak PEC of 2.91, exceeding literature values by 69 %. Additionally, results demonstrated an electrical efficiency of 12.82 % and a thermal efficiency of 40.63 %. Response surface methodology produced highly accurate predictive models (R-2 > 97 % for key parameters) for efficiency and PEC, facilitating geometry optimization without the need for further simulations. Exergy efficiency reached a maximum of 13.77 % for electrical output and 1.7 % for thermal output. Results demonstrated that a decrease in diameter positively impacts all parameters, whereas an increase in the number of holes negatively affects them all.
Keywords: PV/T; Perforated twisted tape; PEC; RSM; Energy and exergy analyses